Development of Dissolution Medium for Glipizide - MANDAL, U.; K. GOWDA, VEERAN; GHOSH, A.; SENTHAMIL SELVAN, P.; SAM SOLOMON, W.D.; PAL, T.K. (Asian Journal of Chemistry, 2010)
Glipizide, an antidiabetic drug is poorly water-soluble. Therefore in vitro dissolution testing of glipizide in water and buffered solutions is not possible. In present study, an attempt was made to develop a new dissolution medium for the in vitro dissolution testing of drug. The selection of the medium was made on the basis of solubility data of glipizide in different medium at 37 ºC. Solubility data revealed that phosphate buffer of pH 6.8 consisting of 0.75 % (w/v) sodium lauryl sulphate could be a suitable dissolution medium.